2012
DOI: 10.1016/j.lindif.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of personality, affect, emotional intelligence and coping with student stress and academic success: Different patterns of association for stress and success

Abstract: a b s t r a c tThe associations of personality, affect, trait emotional intelligence (EI) and coping style measured at the start of the academic year with later academic performance were examined in a group of undergraduate students at the University of Edinburgh. The associations of the dispositional and affect measures with concurrent stress and life satisfaction were also examined. The survey was completed by 238 students, of whom 163 gave permission for their end-of-year marks to be accessed. Complete data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
166
2
27

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(211 citation statements)
references
References 51 publications
16
166
2
27
Order By: Relevance
“…For example, Zeidner (1995) showed that situational emotion-focused coping was related positively to state anxiety whereas problem-focused coping predicted midterm examination grades. Another study by Struthers, Perry and Menec (2000) showed that problem-focused and emotion-focused coping styles were positively related to perceived stress associated with introductory psychology course, and problem-focused coping mediated its effects on college students' motivation which was positively related to academic grades, and similarly, in a recent study (Saklofske, Austin, Mastoras, Beaton, & Osborne, 2012) task-oriented coping was related positively to students' grades.…”
Section: Stress and Coping: The Transactional Perspectivementioning
confidence: 91%
“…For example, Zeidner (1995) showed that situational emotion-focused coping was related positively to state anxiety whereas problem-focused coping predicted midterm examination grades. Another study by Struthers, Perry and Menec (2000) showed that problem-focused and emotion-focused coping styles were positively related to perceived stress associated with introductory psychology course, and problem-focused coping mediated its effects on college students' motivation which was positively related to academic grades, and similarly, in a recent study (Saklofske, Austin, Mastoras, Beaton, & Osborne, 2012) task-oriented coping was related positively to students' grades.…”
Section: Stress and Coping: The Transactional Perspectivementioning
confidence: 91%
“…Support for these findings has also been received in a systematic review of 26 studies on the relationship between emotional intelligence and tertiary academic success (Hanafi et al, 2016). In some studies, specific dimensions of emotional intelligence were found to be positive and strong predictors of tertiary academic success, adaptability (Saklofske, Austin, Mastoras, Beaton, & Osborne, 2012), and understanding of emotion (Mohzan et al, 2013). Overall, it appears to be an important factor of tertiary educational success.…”
Section: Emotional Intelligencementioning
confidence: 80%
“…Meta analyses have noted that the researchers have focused on the big 5 personality traits (Richardson et al, 2012;Vedel, 2014). Among these traits conscientiousness, agreeableness and openness are good predictors of tertiary academic success (Saklofske et al, 2012;Vedel, 2014). The findings of Richardson et al (2012) show that conscientiousness is strongly positively correlated with tertiary academic success and Vedel (2014)'s meta analysis indicates that of these three predictors conscientiousness is the strongest predictor of it.…”
Section: Personality Traitsmentioning
confidence: 99%
“…In any case, coping strategies should have their proper place in current psycho-educational models of learning strategies, since we have seen their potential in helping us understand the role of motivational-affective strategies while learning under academic stress (Saklofske, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%